Some Remarks on Making Use of Ancient Christian Literature in the Study of the Late Roman Economy (the Example of Greek Church Fathers of the Fourth Century) - Milewski, Ireneusz (Studia Ceranea, 2013)
The writings of ancient Christian Writers are still an unappreciated group of sources in the study of the economy of Late Antiquity. They provide a vast amount of information, especially for attentive readers. Within the last fifteen years, neither a monograph nor even a papers concerning some aspects of the Roman economy in the light of the late antique Patristic literature were written (at least not in those widely known and available journals). And the sources have not yet been exploited completely as far as the study of the economy of Late Antiquity is concerned. Also, in many instances, some of the issues should be analysed once more. One needs to take into consideration the progress which was made in the study of the history of the Later Roman Empire in the last years.